A Study on Problems and Prospects in Garment Industry in MP (Journal of Informatics Education and Research, 2024)
India has one of the greatest apparel industries in the world. The door to India's incredibly innovative textile and apparel business is opened by this incredibly well-run sector, which includes garment makers, exporters, suppliers, stockists, and wholesalers. India's ready-to-wear line is incredibly well-liked worldwide. In India, the clothing and textile industries play a special and significant role. The industry, which was among the first in the nation to emerge, is responsible for 14% of the nation's industrial production, almost 30% of its exports, and the creation of jobs, second only to agriculture. Indian clothing has becoming more popular internationally due to its high quality, longevity, and attractiveness.